Long-term survival with pemetrexed-based chemotherapy in a patient with metastatic lung adenocarcinoma of unclear primary origin harboring MTHFR C677T(T/T) mutation: a case report - Yu, Yuan; Li, Nan-Jing; Wang, Jin (Frontiers in Oncology, 2025)
This case report presents a patient with metastatic adenocarcinoma of unclear primary focus at initial presentation and revealed lung adenocarcinoma in subsequent follow-up. The patient has been surviving for more than 10 years after pemetrexed-based treatment and local radiotherapy. Sequential gene tests showed kirsten rat sarcoma viral oncogene homolog (KRAS) G13D mutation and epidermal growth factor receptor (EGFR) 19ins. To further investigate the correlation between pemetrexed efficacy and genetic polymorphisms, genotyping tests on folate-metabolism-related genes [methylenetetrahydrofolate reductase (MTHFR) (C677T) and MTHFR (A1298C)] were performed, revealing that the patient exhibited the T/T genotype for MTHFR (C677T) and the A/A genotype for MTHFR (A1298C). The clinical data and gene analysis were discussed with literature review to explain the underlying explanation for the long survival.